The tariff regulation of railway freight transportation in EU - A.V. Gurzhii; V.O. Timashov; M.Yu. Veselov (Аналітично-порівняльне правознавство, 2024)
The article examines the provisions of the EU legislation on the tariff regulation of rail freight transportation, as well as the prospects of their implementation in the domestic system of industry regulation.